Owner time and cost contingency estimation for building construction projects in Egypt - Nawar, Seif El-Din (AUC Knowledge Fountain, 2017)
Time and cost overruns are an integral part of the construction projects. Both have several associated negative consequences to the project owners. Setting the right time and cost contingency is a major contributing factor to the success of the project as it should minimize/prevent budget and time overruns. Project managers usually tend to allocate project time and cost contingency subjectively based on their previous experience and may not capture all projects specific factors that impact the contingency estimation. The competency of the project manager plays an important role in this case in determining the contingency percentage. The contingency estimation for a given project can hugely vary from one project manager to another. This research presents a fuzzy logic-based model that allows owners predict the project time and cost contingency reliably and accurately in Egypt. The most important factors affecting time and cost contingency have been identified and are defined as input variables for the model. The effect of these factors on the time and cost contingency, the output variables, have been determined and incorporated into the model via fuzzy rules. On the basis of the known effects of these factors, a fuzzy logic model is developed to automate the prediction process using MS Excel software. Several scenarios of the model are developed and subjected to initial testing using 10 actual projects data. Based on the initial testing, the best model was subjected to tuning in order to achieve the optimum model results in terms of accuracy and validity. Finally, the model is tested by applying it on new five actual construction projects which were not used in the initial testing nor tuning. The model results were found to be acceptable having an average validity percent of 84% and 81% for time and cost contingency, respectively. The proposed model allows the owners to [1] understand the effect of the project different factors on the contingency values, which in turn represent the degree of risk involved and accordingly, allows the owner to take necessary measures at the preconstruction stage to reduce the risks, [2] minimize the cost and time overrun through setting the right amount of contingency, [3] avoid tie up of excessive funds for the project, which can be used in others projects or activities, and [4] have higher confidence during the decision making process of whether to proceed or not to proceed with the project.